RELATIVE IMPORTANCE INDEX OF LEADING INDICATORS FIRE PROTECTION SYSTEMS IN HIGHER EDUCATION BUILDINGS IN KOTA BANDA ACEH - Fatima , Rahel; Oktaviani, Cut Zukhrina; Bulba, Alfa Taras (Universitas Trisakti, 2024)
Fire can cause material loss and also cause physical disabilities and even fatalities for building users. Fires that occur as a result of human activity must be overcome by increasing human awareness themselves. However, fires caused by natural factors or errors in the electrical system can be overcome by having a fire prevention system or safety system. The aim of the research is to identify the main indicators of fire protection systems in educational buildings in Banda Aceh City. A closed questionnaire and Likert scale survey of respondents using educational buildings was conducted to collect data. Next, the data is processed using the frequency index analysis method and the Relative Importance Index (RII). The results of the frequency index analysis provide an overview of the percentage level of occurrence of the fire protection system variable, namely the acid detector, at 91.294%. Based on the results of the RII analysis, five main indicators were found that influence the safety system, namely light fire extinguishers (0.929), smoke detectors (0.913), water transmitters (0.911), standpipes (0.894), and fire hydrant systems (0.892). Meanwhile, the main variable for the fire protection system is the active protection system with a RII value of 0.889.